Strategi Mitigasi Dampak Penurunan Kualitas Udara Dari Rencana Kegiatan Pembangkit Listrik Tenaga Panas Bumi (PLTP) X Di Dataran Tinggi Jawa Barat - Hendrayana, Yayan; Sodikin, Sodikin; Rusdiyanto, Edi (Jurnal Teknologi Lingkungan Lahan Basah, 2026)
The planned development of a Geothermal Power Plant (PLTP) in the West Java Highlands is part of national efforts to accelerate the transition toward renewable energy and reduce dependence on fossil fuels. Although geothermal energy is considered a clean energy source, PLTP operations may still have environmental impacts, particularly the degradation of ambient air quality due to non-condensable gas emissions such as hydrogen sulfide (H₂S) and ammonia (NH₃). This study aims to develop technical–social mitigation strategies using a SWOT-based approach to reduce the risk of H₂S and NH₃ exposure in residential areas within a 1-km radius of the proposed PLTP operational site. A mixed-methods approach was employed, utilizing both primary and secondary data. Primary data were obtained from respondent perceptions through interviews with stakeholders involved in the PLTP development, while secondary data were collected from documents, journals, and other relevant sources. A SWOT analysis was conducted to assess mitigation strategies, considering internal and external factors influencing air quality management. The findings produced four strategic directions: (1) optimizing emergency gas-leak procedures through SOP updates, integrating real-time emission monitoring via the installation of a Continuous Emission Monitoring System (CEMS), and implementing a Gas Removal System (GRS) with an efficiency of ≥90%; (2) strengthening community capacity through gas-mitigation training and SOP dissemination supported by CSR programs; (3) enhancing early detection of H₂S leaks through the use of accurate monitoring instruments and adjusting monitoring locations based on extreme meteorological conditions; and (4) improving public preparedness through AMDAL disclosure, establishment of village emergency posts, and periodic updates of emergency protocols. This study concludes that for the planned PLTP project in the West Java Highlands, recommended mitigation strategies should focus on a combination of technical, social, and institutional measures, emphasizing preventive monitoring, community engagement, and the adoption of environmentally friendly technologies to support sustainable geothermal development.